Design Optimization of Biocrust-Plant Spatial Configuration for Dry Ecosystem Restoration Using Water Redistribution and Erosion Models - Maggioli, Lisa; Rodríguez-Caballero, Emilio; Cantón, Yolanda; Rodríguez-Lozano, Borja; Chamizo, Sonia (Frontiers in Ecology and Evolution, 2022)
Land degradation is one of the main threats to dryland sustainability in the next decades, hence restoration of the degraded land from drylands is an urgent need to maintain ecosystem functionality and their ability to provide ecosystem services of the largest terrestrial biome. However, dryland restoration is challenging due to the frequent environmental stresses that constrain vegetation survival and growth in these ecosystems. Drylands function as complex ecohydrologically coupled systems in which interplant source areas, frequently covered by biocrusts, act as sources of runoff and nutrients to adjacent vegetation, which act as sinks for these resources. Thus, one way to increase dryland restoration success is through an optimal configuration of biocrusts and plants that maximizes an efficient use of the limited resources within the system. In this study, we selected a degraded slope from a limestone quarry located in Almeria province (SE Spain) and modeled how active restoration of the biocrust through soil inoculation with cyanobacteria and its combination with different spatial configurations of vegetation affected runoff redistribution and erosion. For that, we applied the spatially distributed Limburg Soil Erosion Model (LISEM) which was able to predict the erosion measured on the slope during the study period with low error (RMSE=17.8%). Modeling results showed that the introduction of vegetation on the degraded slope reduced runoff between 2 and 24% and erosion between 4 and 17% for the scenario with plants compared to the one without restoration management. Of all the vegetation spatial configurations tested, the one that provided better results was the scenario in which plants were located in the areas of higher water accumulation (higher topographic wetness index). Moreover, we found that active biocrust restoration by cyanobacteria inoculation significantly reduced erosion by 70-90%, especially during the first stages of plant development, while maintaining water supply to vegetation. These findings highlight the potential of water redistribution and erosion simulation models to identify the most optimal spatial configuration of ground covers that maximizes water and nutrient supply to vegetation, while minimizes water, sediment, and nutrient losses by erosion, thus serving as an efficient tool to plan restoration actions in drylands.